Advances in the monitoring of the SiO2 evaporation loss in transparent YAG ceramics by LIBS. Issue 9 (15th June 2019) - Hostaša, Jan; Piancastelli, Andreana; Biasini, Valentina; Pandey, Sudeep Jung; Martinez, Mauro; Baudelet, Matthieu; Gaume, Romain
Abstract: The effect of silica on the densification of transparent YAG ceramics has long been investigated. The present paper makes a step forward on the quantification of the Si amount in YAG. The study shows how to measure with a high level of accuracy the silicon concentration in YAG in different steps of the fabrication process. The Laser-Induced Breakdown Spectroscopy (LIBS) has been used to quantify the amount of silicon in a set of samples with 0–0.275 wt% silica. Nanometric silica soot or its precursor, TEOS, has been used as silica source. The analysis shows that more than 80 wt % of SiO2 evaporates during reactive-sintering under vacuum, most probably because SiO gas forms during sintering under low oxygen partial pressure. In-depth concentration maps were obtained by laser drilling with LIBS pulses. The results show the possibility to modify the amount of residual Si in YAG ceramics by adjusting the sintering and annealing process.